A Centralized Accounting Method of Enterprise Accounting Cost Based on Fourier Transform Algorithm. (10th September 2022) - Fan, Xiao'e
Abstract : With the rapid development of the economy, the challenges faced by enterprises are becoming more and more severe. In order to enhance the core competitiveness of enterprises themselves, enterprises pay more and more attention to accounting cost accounting. However, for a long time, enterprises have been using traditional accounting costing methods, which greatly hampered the development of enterprises. The Fourier transform (FT) algorithm is a commonly used information transformation method, which can simplify the complex cost accounting process. Based on this, this paper proposes a centralized cost accounting method for enterprise accounting based on FT algorithm, aiming to fundamentally change the traditional cost accounting thought. The article first analyzes and summarizes the general characteristics of cost accounting methods. Then, starting from the cost centralized accounting method, the paper optimizes the traditional cost accounting formula by using the FT algorithm and proposes a new accounting cost-centralized accounting formula based on the FT algorithm. Finally, starting from the reality and taking W company as the research object, the article focuses on analyzing the application of the centralized accounting method of accounting cost relying on the FT algorithm in the production and operation activities of the actual enterprise. After a series of experiments and analysis, we found that the centralized cost accounting method of enterprise accounting based on FT algorithm has a very high degree of fit with the actual situation, and the accuracy of cost accounting is as high as 70.01%. Moreover, in the process of enterprise cost analysis, the quality of accounting information of enterprises has been comprehensively improved by 31.9%. This fully shows that the centralized accounting method of enterprise accounting cost based on the FT algorithm can bring certain economic benefits to the enterprise and optimize the internal resource allocation of the enterprise.